2020
DOI: 10.1021/acs.iecr.0c02732
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Mechanism Study on Destruction of the Simulated Waste Ion-Exchange Resin from the Nuclear Industry in Supercritical Water

Abstract: The optimization and mechanism for oxidation of the waste anion exchange resin from the nuclear industry in supercritical water were investigated. To achieve the maximum chemical oxygen demand (COD) and total nitrogen (TN) removal efficiencies, the response surface methodology (RSM) was employed to optimize four operating variables. Two quadratic polynomial models with satisfactory accuracy were established based on the experimental results. Under optimized conditions, the removal rates of the COD and TN could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…16,17 In recent years, researchers have conducted comprehensive investigations on SCWO treatment of radioactive organic waste. Xu et al 18 investigated the optimization of the waste anion exchange resin from the nuclear industry in SCW. Under optimized conditions, the removal rates of the COD and TN could reach up to 99.91% and 36.02%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In recent years, researchers have conducted comprehensive investigations on SCWO treatment of radioactive organic waste. Xu et al 18 investigated the optimization of the waste anion exchange resin from the nuclear industry in SCW. Under optimized conditions, the removal rates of the COD and TN could reach up to 99.91% and 36.02%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the chemical oxygen demand (COD) removal rate of the waste resin was 99.9%, and there were no radioactive nuclides in the waste gas. 21 Researchers have primarily focused on TBP regarding the challenging problem of radioactive organic liquid waste treatment generated from nuclear power plants and spent fuel reprocessing. Yang and Zhang found that the gaseous product of TBP degradation is CO 2 , while the liquid products include PO 3 -4…”
Section: Introductionmentioning
confidence: 99%
“…studied the degradation process of nuclear industry anion exchange resin in SCWO. The results showed that the chemical oxygen demand (COD) removal rate of the waste resin was 99.9%, and there were no radioactive nuclides in the waste gas 21 . Researchers have primarily focused on TBP regarding the challenging problem of radioactive organic liquid waste treatment generated from nuclear power plants and spent fuel reprocessing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, different oxidant including air, O 2 , and H 2 O 2 are applied into the superheated water during supercritical water oxidation (SCWO) that not only increase the operational cost but also enhance energy demand (500-700°C) (Huelsman andSavage, 2013, Zhang et al 2020a). However, the proper usage of catalysts could effectively improve the oxidant concentration and reactor energy demand without affecting the operational performance (Xu et al 2020). An appropriate catalyst not only improves the removal of chemical oxygen demand (COD) of the waste but also enhances the selectivity of phenols into CO 2 , CH 4 , and H 2 (Nadjiba et al 2017 (Abdpour and Santos, 2020, De Silva et al 2017, Huelsman and Savage, 2013.…”
Section: Introductionmentioning
confidence: 99%